Determination of Level of Ag, Cu, and Fe in the Mineral Rock Coming from Jambu Dolok Hamlet Toba Samosir District - Alva, Sagir (Talenta Publisher, 2021)
A study on the determination of Ag, Cu, and Fe contents in mineral rocks has been conducted. The sample was randomly taken from the surface of the hill at Dusun Jambu Dolok Kabupaten Toba Samosir. Ovens destroyed the sample at 900Â°C. For the determination of Ag and Cu, the sample was dissolved by using concentrated HNO3. For the determination of Fe, it was dissolved by using concentrated HNO3 and concentrated HCl. The determination of Ag, Cu, and Fe was carried out using Atomic Absorption Spectrophotometer. The wavelength is 328.1 nm for Ag, 324.7 nm for Cu, and 248.3 nm for Fe. The results obtained show that the content of Ag, Cu, and Fe in the sample are 2.1590 mg/Kg, 21,311.4754 mg/Kg, and 150,000.0000 mg/Kg, respectively